2006
DOI: 10.1002/jcp.20905
|View full text |Cite
|
Sign up to set email alerts
|

CCL20 chemokine induces both osteoblast proliferation and osteoclast differentiation: Increased levels of CCL20 are expressed in subchondral bone tissue of rheumatoid arthritis patients

Abstract: We evaluated the role of CCL20 (MIP-3alpha) chemokine in cells directly involved in the remodeling of bone tissue (osteoblasts and osteoclasts) and we confirmed its expression in the subchondral bone tissue of rheumatoid arthritis (RA) patients. The expression of CCL20 and of its receptor CCR6 was evaluated in osteoblasts isolated from bone tissue of post-traumatic (PT) patients. Functional tests were performed to evaluate osteoblast proliferation and matrix protein modulation. Immunohistochemical analysis for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 41 publications
4
44
1
Order By: Relevance
“…Human osteoblasts (hOB) were isolated from the iliac crest biopsies obtained from healthy or MGUS patients after collagenase digestion according to the method used by Robey and Termine, as previously published (20,23). hOBs were fixed in 4% paraformaldehyde and analyzed using a FACStar Plus cytometer (Becton Dickinson) for the expression of osteoblast markers.…”
Section: Cells and Cell Culture Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Human osteoblasts (hOB) were isolated from the iliac crest biopsies obtained from healthy or MGUS patients after collagenase digestion according to the method used by Robey and Termine, as previously published (20,23). hOBs were fixed in 4% paraformaldehyde and analyzed using a FACStar Plus cytometer (Becton Dickinson) for the expression of osteoblast markers.…”
Section: Cells and Cell Culture Conditionsmentioning
confidence: 99%
“…CC-chemokine ligand 20 (CCL20)/MIP-3a and its selective receptor CC-chemokine receptor 6 (CCR6), known to be responsible for the chemoattraction of dendritic, T, and B cells in homeostatic conditions (17), have been recently involved in rheumatoid arthritis synovitis (17)(18)(19) and OC activation in rheumatoid arthritis patients being overexpressed in subchondral bone tissues (20). Moreover, it has been shown that the overexpression of CCR6 by Langerhans cells in malignant histiocytosis contributes to their accumulation in the bone together with CCL20/MIP-3a overproduction by osteoblasts in the involved bone (21).…”
Section: Introductionmentioning
confidence: 99%
“…It also attracts OCPs to bone surfaces, and activates T lymphocytes and synovial fibroblasts in RA to secrete RANKL [43,60,78]. CCL20 is over-expressed in subchondral bone in RA, and is able to induce OCP expansion and osteoclast differentiation [79] Although treatment of RA patients with anti-CCL2 antibody failed to produce clinical improvement, recent studies revealed that serum CCL2 level is associated with osteoclastogenic potential of peripheral blood OCPs and clinical markers of arthritis activity [52,80].…”
Section: Effect Of Arthritic Mediators On Osteoclast Progenitorsmentioning
confidence: 99%
“…In addition, CCL20 also promotes tumor cell invasion by upregulation of MMP9 in pancreatic cancer cells (22), increases proliferation of colorectal cancer cells (23), and stimulates osteoblast cell growth (24). Thus, we examined the effect of CCL20 on breast cancer cells.…”
Section: Ccl20 Increases Migration and Invasiveness Of Mda-mb-231 Celmentioning
confidence: 99%